Pengaruh Lingkungan Teman Sebaya Terhadap Perilaku Sosial Remaja Usia 16-19 Tahun - Amsah, Dara Gustia; Sugi Pawira, Elsa Adinda Suci; Qauli, Syahmara; U, Usiono (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The influence of peer environment on the social behavior of adolescents aged 16-19 years is the focus of this study. This study aims to identify the extent to which peers influence adolescent social behavior, both in positive and negative aspects. The research method used is a survey involving a number of adolescents as respondents. The results of the study indicate that the peer environment has a significant influence on adolescent social behavior. Peers can be role models, sources of social support, and also sources of pressure to take certain actions. This study concludes that the peer environment is an important factor that needs to be considered in understanding adolescent social development.